Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0168291
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Thermal Acclimation, Growth Rate, and Phylogeny Influence Prochlorococcus Elemental Stoichiometry

Abstract: Variability in plankton elemental requirements can be important for global ocean biogeochemistry but we currently have a limited understanding of how ocean temperature influences the plankton C/N/P ratio. Multiple studies have put forward a ‘translation-compensation’ hypothesis to describe the positive relationship between temperature and plankton N/P or C/P as cells should have lower demand for P-rich ribosomes and associated depressed QP when growing at higher temperature. However, temperature affects many c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 44 publications
9
40
1
Order By: Relevance
“…Agreement between cellular P quotas (1.1 ± 0.4 x 10 7 atoms per cell) and literature data for this strain (0.4-0.7 x 10 7 atoms per cell (Martiny et al, 2016)) and Prochlorococcus Med4 (0.2-2 x 10 7 atoms per cell, (Bertilsson et al, 2003)) indicate that ICPMS and flow cytometry determinations are robust. The 1.7 M bp genome of Prochlorococcus MIT9215 alone accounts for 0.3 x 10 7 P atoms per cell, a considerable fraction of the cellular P quota.…”
Section: Measuring Cell Quotas By Inductively Coupled Plasma Mass Spesupporting
confidence: 63%
“…Agreement between cellular P quotas (1.1 ± 0.4 x 10 7 atoms per cell) and literature data for this strain (0.4-0.7 x 10 7 atoms per cell (Martiny et al, 2016)) and Prochlorococcus Med4 (0.2-2 x 10 7 atoms per cell, (Bertilsson et al, 2003)) indicate that ICPMS and flow cytometry determinations are robust. The 1.7 M bp genome of Prochlorococcus MIT9215 alone accounts for 0.3 x 10 7 P atoms per cell, a considerable fraction of the cellular P quota.…”
Section: Measuring Cell Quotas By Inductively Coupled Plasma Mass Spesupporting
confidence: 63%
“…They attributed the observed rise in algal N:P and C:P ratios, with rising temperatures, to decline in cellular quotas of P-rich assembly machinery (ribosomes), relative to N-rich light harvesting machinery (chloroplasts and proteins), with increasing temperature. On the contrary, Martiny et al [65], showed that thermal effect leads to increased cellular quotas of nitrogen and carbon, whereas the cellular phosphorous quota changes very little in the marine cyanobacterium, Prochlorococcus. Their results point towards other physiological acclimation mechanisms as the principal drivers of elemental changes in Prochlorococcus.…”
Section: Effects Of Ocean Warming On Phytoplankton Stoichiometry and mentioning
confidence: 98%
“…Temperature has been shown to positively correlate with C:P and N:P ratios, but not with C:N. These shifts occur because fewer P-rich ribosomes are required at warmer temperatures due to their increased use efficiency [62,63,67,68]. However, elevated C and N content and a decrease of P have also been attributed to observed stoichiometric changes in warm-acclimated phytoplankton cells [69]. Hence, more than one process potentially causes temperature-dependent shifts in elemental ratios.…”
Section: Temperaturementioning
confidence: 99%